Dynamic Analysis of Sandwich Cylindrical Shell - Cabanska-Placzkiewicz, K. (Проблемы прочности, 2000)
We present dynamic analysis of cylindrical shells and study new mechanical effects in distribution of stresses, strains and displacements. Cylindrical shells are studied in the framework of Kirchhoff-Love hypothesis and the refined Timoshenko model.